2011
DOI: 10.2319/040811-250.1
|View full text |Cite
|
Sign up to set email alerts
|

Dehiscence and fenestration in skeletal Class I, II, and III malocclusions assessed with cone-beam computed tomography

Abstract: The null hypothesis was rejected. Significant differences in the presence of fenestration were found among subjects with skeletal Class I, Class II, and Class III malocclusions. Fenestrations had greater prevalence in the maxilla, but more dehiscences were found in the mandible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
135
7
24

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(181 citation statements)
references
References 31 publications
9
135
7
24
Order By: Relevance
“…26 Similarly, dehiscences and fenestrations were assessed with CBCT in skeletal Classes I, II, and III malocclusions. 25 The Class II group had a greater prevalence of fenestrations, and dehiscences were seen with a high frequency in the mandibular incisors of all groups. In another study, 9 these bony defects were examined in terms of vertical growth patterns using CBCT; the prevalence of dehiscences was higher in the hyperdivergent group than in the hypodivergent group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Similarly, dehiscences and fenestrations were assessed with CBCT in skeletal Classes I, II, and III malocclusions. 25 The Class II group had a greater prevalence of fenestrations, and dehiscences were seen with a high frequency in the mandibular incisors of all groups. In another study, 9 these bony defects were examined in terms of vertical growth patterns using CBCT; the prevalence of dehiscences was higher in the hyperdivergent group than in the hypodivergent group.…”
Section: Discussionmentioning
confidence: 99%
“…Although Sun et al 12 reported that this method might overestimate the actual measurements, the technique was reported to have the highest sensitivity and diagnostic accuracy for detecting various periodontal defects. 21 A few studies 9,25,26 have analyzed dehiscences and fenestrations by CBCT in different malocclusion groups and normal populations. However, no data were available for patients with clefts.…”
Section: Discussionmentioning
confidence: 99%
“…Este tratamento tem apresentado bons resultados periodontais a longo prazo (NORDQUIST, MCNEILL, 1975;SILVA FILHO et al, 2000), quando o canino adjacente é mesializado para a região de incisivo lateral, tomando os devidos cuidados durante a reanatomização para torná-lo o mais parecido possível com um incisivo lateral. Enquanto um dente é ortodonticamente movimentado pelo alvéolo, ocorre uma remodelação óssea em volta da raiz, (ZACHRISSON, 2003) GARIB et al, 2006;GRACCO et al, 2009;NAUERT, BERG, 1999;RUNGCHARASSAENG et al, 2007;SARIKAYA et al, 2002;VASCONCELOS et al, 2012;YATABE, 2010) KING, 1990;DORFMAN, 1978;GARIB et al, 2006;GEIGER, WASSERMAN, 1980;HOLLENDER, RONNERMAN, THILANDER, 1980;PERSSON, LENNARTSSON, 1986;SHARPE et al, 1987;SJOLIEN, ZACHRISSON, 1973;THILANDER, 1992;YAGCI et al, 2012;ZACHRISSON, ALNAES, 1973, 1974 Quando uma pressão é aplicada ao dente, leva a uma alteração no fluxo sanguíneo do ligamento periodontal, que diminui onde o ligamento é comprimido e é mantido ou aumentado onde o ligamento está sob tensão. As alterações químicas, agindo diretamente ou por estímulo da liberação de outros agentes ativos biologicamente, estimulam a diferenciação e a atividade celular.…”
Section: Lista De Figurasunclassified
“…Dessa forma, pode-se observar que os dentes caninos e incisivo lateral superior apresentam, em geral, uma espessura da tábua óssea vestibular mais estreita do que a lingual, corroborando os estudos descritos na literatura. (DEGUCHI et al, 2006;EDEL, 1981;EVANGELISTA et al, 2010;LARATO, 1970;LIM et al, 2009;MOTOYOSHI et al, 2009;MOTOYOSHI et al, 2007;PARK, CHO, 2009;RUPPRECHT et al, 2001;VOLCHANSKY, CLEATON-JONES, 1978;YAGCI et al, 2012) Os caninos movimentados para a região do enxerto apresentaram uma tábua óssea mais estreita do que os caninos e incisivos laterais localizados no quadrante sem fissura, porém com diferença estatisticamente significante apenas para a face …”
Section: A Amostraunclassified
See 1 more Smart Citation